1995
DOI: 10.1159/000236848
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Epstein-Barr Virus and Cytomegalovirus Genome in White Blood Cells from Patients with Juvenile Rheumatoid Arthritis and Childhood Systemic Lupus Erythematosus

Abstract: The role of infectious agents in the pathogenesis of autoimmune diseases has long been a matter of debate. This study investigated the possible role of Epstein-Barr virus (EBV) and human cytomegalovirus (HCMV) infections in the pathogenesis of autoimmune diseases by an attempt to demonstrate the presence of the viral genome in the leukocyte of 21 juvenile rheumatoid arthritis (JRA) patients, 20 childhood-onset systemic lupus erythematosus (SLE) patients, and 20 age-matched normals, using polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 15 publications
(16 reference statements)
1
28
2
Order By: Relevance
“…Number of studies showed that SLE patients had higher anti-EBV response and EBV DNA burden [6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Number of studies showed that SLE patients had higher anti-EBV response and EBV DNA burden [6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…When the expected true seronegative rate in adults is ϳ5%, even a false-negative rate of only 5% in detecting seroconversion against EBV will wreak havoc with the power of a study to detect an effect that is present. This means that studies that showed a possible association (14)(15)(16), as well as those that did not (17)(18)(19), contained too few SLE patients and controls to reliably and reproducibly detect a difference. In addition, only one of the previous studies used the strategy of evaluating children and adolescents (19), which would increase the ability to detect associations.…”
Section: Discussionmentioning
confidence: 99%
“…This means that studies that showed a possible association (14)(15)(16), as well as those that did not (17)(18)(19), contained too few SLE patients and controls to reliably and reproducibly detect a difference. In addition, only one of the previous studies used the strategy of evaluating children and adolescents (19), which would increase the ability to detect associations. However, this study was also underpowered and used an anti-EBV antibody assay and EBV DNA assay technologies that were even older and less reliable.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Environmental triggers such as viral infections have been suggested, [4][5][6] but other studies have not substantiated these findings. [7][8][9][10] One study found that hospitalization for infection in the first year of life was associated with an increased risk of developing JIA. 11 However, this study focused on hospital-based diagnoses and not on antibiotic use, thus limiting its interpretability.…”
Section: What's Known On This Subjectmentioning
confidence: 99%